A Time Course Study of Different Methods of Extraneural Scar Induction in a Rat Model - Zanjani, Leila Oriady; Firouzi, Masoumeh; Nabian, Mohammad Hossein; Zadegan, Shayan Abdollah; Nategh, Mohsen; Erfanian, Reza; Ashtiani, Ahmad Mohebbi; Kamrani, Reza Shahryar (Journal of Reconstructive Microsurgery, 2016)
Background Extraneural scar formation is a challenging problem in nerve repair. Rodent models of scar induction, with their high regenerative capacity, suffer from lack of comparable similarities with human cases. In this study, we attempted to find a reliable and reproducible method of extraneural scarring with a significant impact on the peripheral nerve function.Methods A total of 60 rats were divided into three scar induction groups: abrasion (with a small piece of compressed steel wool), mincing (with extracorporeal mincing of adductor muscle and a 5-mm wide strip of the anterior border of the biceps femoris), and electrocoagulation (with a bipolar coagulator). Extraneural scarring was evaluated macroscopically and histologically during 8 weeks. The tibial functional index was used for behavioral analysis.Results Among three different physical methods of scar induction that were applied, electrocoagulation had the most functional impairment (p < 0.001, two-way analysis of variance); whereas mincing produced the most adhesive and intensive scar, morphologically (p < 0.001).Conclusion We conclude that: (1) the impact of the extraneural scar on the nerve is morphologically and functionally different, based on the method of scarring; (2) to achieve a scar model comparable to the human situation, a method in which the involved nerve is functionally impaired, is preferred over the ones that merely produce a bulky scar.
Keywords: peripheral nerve; sciatic nerve; scar; regeneration; experimental model